Urgensi Desentralisasi Partai Politik (Studi Kasus Kekosongan Jabatan Wakil Bupati Kampar Periode Sisa 2017-2022) - Era Refani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Reformasi that brought democratization spirit been an entrance for the implementation of decentralization to the region. Since that region has the wider authority to run the local government. However authority-decentralization is not accompanied with the implementation of political party decentralization to the regon. The centre political leaders often make a centralized decision like the determination of prospective regional head candidate. Political party at region becomes not independent so that unable to run the recruitment function and the weakness political bargaining in negociate to coalition.This qualitative research uses library research technique by collecting data and fact from the relevant source in the intention to analyze the relation of political party decentralization with the filling the position of deputy regent of Kampar remaining periode 2017-2022.The process of filling the position of deputy regent which is complicated shows that the political party in region has the weakness in negotiation added with inability to bring emas agent. 6 political parties in Kampar Maju Coalition that supported Aziz-Catur in Pilkada Kampar 2017 is rated corpulent so that it needs to considersing vary choices and interests. UU Nomor 10 Tahun 2016 is not even giving the time limit on filling the vacant position with the result that coalition of political parties are not working as soon as possible. On the other side, many are demanding the acceleration of filling the post of deputy regent of Kampar.